Effects of yoga exercise combined with passive stretching on the flexibility and strength of female students - Nattaprida Palanao; Kritpech Nontakhod; Nattapong Kusadet; Anchisa Thongthuedee; Kampeeraphab Intanoo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Exercise combining yoga with passive stretching (YPS) represents an alternative approach to enhancing health and physical fitness, particularly in terms of improving flexibility and muscular strength. However, there remains a scarcity of research investigating the effects of this combined exercise modality specifically within female student populations.